Investigating the Impact of Counselling and Guidance Services on Pregnant Mothers Attororo General Hospital, Uganda - Caroline Omella (Uganda Christian University, 2025)
The utilization of guidance and counseling services by pregnant mothers has until today continued to register downward trend. This study investigated the impact of Counseling and Guidance services on pregnant mothers at Tororo general hospital. Specifically, the study explored the importance of guidance and counseling services to pregnant mothers and why pregnant mothers don’t use guidance and counseling services. The study used a mixed research approach and descriptive study design to analyze data from the study area with the help of both qualitative and quantitative methods. The researcher collected data from 20 respondents in the study area who were selected using simple random and purpose sampling and questionnaires together with interview guides were used to collect data. The study found that guidance and counseling services improves mental health of pregnant mothers and enhances healthcare seeking behavior and also help to reduce maternal and infant mortality. Findings also revealed that guidance and counseling services lowers stress among pregnant women. Further, study findings also show that that long distances to health facilities prevents pregnant women from accessing guidance and counseling services and stigma prevents utilization of counseling services by pregnant women. Poverty according to the findings also prevents pregnant mothers from using guidance and counseling services and lack of male involvement prevents utilization of counseling services. The study recommended that there is need to reduce on long distances to health facilities by government and service providers as this prevents pregnant women from accessing guidance and counseling services and government and stakeholders should put in place interventions to address stigma as it prevents utilization of counseling services by pregnant women. Other recommendations included poverty reduction strategies should be implemented by government and stakeholders so as to increase pregnant mothers’ level of utilization of guidance and counseling services and community sensitization should be undertaken to increase male involvement as lack of this ultimately prevents utilization of counseling services.